1996
DOI: 10.1351/pac199668020275
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new molecular systems

Abstract: The versatile cyclopropene synthon 1 -bromo-2-chlorocyclopropene has been used to synthesize new di-and tricycloproparenes. Treatment of these cycloproparenes with silver ion in chloroform leads to rapid oligomerization via carbocation intermediates to give materials in which the aromatic systems are connected by six-membered rings. The ladder polymer formed by treating the linearly fused dicyclopropanaphthalene with silver ion in chloroform has been characterized by solid state nuclear magnetic resonance spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…However, the provision of such derivatives by dimerization of lower members of the series has been achieved (see section IIIA). 101 If an appropriate multiple cissoid diene is available then there appears to be almost no limit to the way in which the cycloproparene moiety can be incorporated into organic structures. Thus, Billups 102 has show that the symmetrical tricycloproparenes 76 and 77 (Chart 1) can be obtained from hexaradialene 85 and hericene 86, respectively, by way of 3-fold Diels-Alder cycloadditions with 60.…”
Section: By Employing 16-dihalo Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the provision of such derivatives by dimerization of lower members of the series has been achieved (see section IIIA). 101 If an appropriate multiple cissoid diene is available then there appears to be almost no limit to the way in which the cycloproparene moiety can be incorporated into organic structures. Thus, Billups 102 has show that the symmetrical tricycloproparenes 76 and 77 (Chart 1) can be obtained from hexaradialene 85 and hericene 86, respectively, by way of 3-fold Diels-Alder cycloadditions with 60.…”
Section: By Employing 16-dihalo Derivativesmentioning
confidence: 99%
“…63,206 Silver(I) also promotes the addition of alkenes, alkynes, allenes, and conjugated dienes to cyclopropabenzene as has been discussed earlier, 15 and this ion, Cu(II), and Hg(II) have been used in the dimerization of 2. 101,207,208 Nonetheless, it is the use of Ag(I) in the linear dimerization of the cycloproparenes that now commands most attention. 100,101,103,209 In 1974, Billups 207 showed that Ag(I) effected smooth dimerization of 2 to 9,10-dihydroanthracene.…”
Section: A With Electrophiles Nucleophiles and Radicalsmentioning
confidence: 99%
“…Rather, the first derivatives were subjected to silver(I) in methanol in a study 23 that predates the dimerization work of Billups. [15][16][17][18] To date this gap has not been bridged. Thus complexation of, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…That the reaction conditions employed herein are appropriate for dimerization has been confirmed from successful dimerization of 3 to 6,13-dihydropentacene in 73% yield. 15,17 The steric constraints present at C1 of the exocyclic alkenes 1-5 (and disilane 4) are too large to allow dimerization as only products of ring opening (or unchanged starting material) are recorded .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation